Comparison of severity of COVID-19 symptoms in Vaccinated versus Unvaccinated people; A Retrospective Cross-sectional study - Shahzad, Faizan; Aman Nasir, Haider; Yousaf, Ayesha; Qasmi, Amina; Nayyar, Neha; Intisar, Rana Fahd (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. SARS-CoV-2, also known as severe acute respiratory syndrome coronavirus 2. Several vaccines against COVID-19 have been developed, yet people still hesitate to get vaccinated. There were concerns mainly regarding the safety, and partly the efficacy of vaccination against COVID-19. This research is intended to compare the severity of COVID-19 symptoms in vaccinated individuals against unvaccinated ones. Methods: A retrospective cross-sectional study was conducted among total 720 individuals in 2 groups i.e., vaccinated and unvaccinated each comprising of 360 persons. the vaccinated and unvaccinated. The study was conducted in the Department of Medicine at Benazir Bhutto Hospital (BBH) Rawalpindi. Data was collected from the hospital records of BBH and NADRA (National Database & Registration Authority) Covid Helpline “1166”. Chi-Square Test was applied to measure the relationship between vaccination status and severity of symptoms. P<0.05 was taken as significant. Results: 63% of patients who experienced moderate symptoms and 57.1% of patients who experienced severe symptoms were vaccinated, whereas 56.5% of critical and 60% of patients who died were unvaccinated (P=0.002). The patients were divided into groups according to age as well. A total of 4 such groups were made. 52.1%. Individuals in Group 1 (18 to 37 years of age) experienced moderate symptoms whereas 51.3% of individuals in Group 4 (78 to 97 years of age) died. Conclusion: A significant relationship between decreased severity of symptoms and vaccination status was observed thus reinforcing the efficacy of vaccination against COVID-19.